Enemy of my enemy - Segura, Alex, 1980- (Marvel crime., 2026)
"When the call comes in that the Kingpin and a police officer have been killed and that Frank Castle (aka the Punisher) has turned himself in for it, Matt senses holes in the narratives the media and the streets are quick to run with. Both criminals have been Matt's nemeses when he dons the cowl of the Daredevil, and there's no denying that New York is better off without its Kingpin and the Punisher behind bars. And yet, while the Punisher is a murderous vigilante, he doesn't kill cops. And he doesn't turn himself in. Castle certainly deserves prison for all of the other crimes he has committed in the past. However, Matt's indominable sense of justice insists that nobody should be sent to prison for crimes they didn't actually commit. Representing the vigilante in court, Matt enters a contest of wills and guile with Castle to try and uncover the game beneath the game. And when Matt's girlfriend takes the stand and complicates matters, there's truly no rest for the wicked or the just. As the Kingpin's absence has passions running hot in Hell's Kitchen, Matt must decide if justice means the letter of the law, what's best for the citizen on the streets, or where is heart is beginning to lead him."--